Politics and Cultures of Liberation Media, Memory, and Projections of Democracy - Bak, Hans; Mehring, Frank; Roza, Mathilde (Radboud Studies in Humanities, 2018)
Politics and Cultures of Liberation: Media, Memory, and Projections of Democracy focuses on mapping, analyzing, and evaluating memories, rituals, and artistic responses to the theme of "liberation." The contributors offer a wide range of diverse intercultural perspectives on media, memory, liberation, (self)Americanization, and conceptualizations of democracy. Readership: This book is crucial for scholars and students of transnational studies, media studies, literature, history, and cultural studies who are interested in socio-cultural and political constructions of Europe and "America."